A Systematic Review of Dynamic Forces and Kinematic Indicators of Front and Roundhouse Kicks across Varied Conditions and Participant Experience - Michal Vagner; Daniel John Cleather; Vladan Olah; Jan Vacek; Petr Stastny (MDPI AG, 2023)
Impact force and maximum velocity are important indicators of kick efficiency. Therefore, this systematic review compared the front kick (FK) and roundhouse kick (RK), including their impact force, maximum velocity, angular velocity, and execution time, considering various target types and experience levels. Following PRISMA guidelines, the Web of Science, SportDiscus, and PubMed were systematically searched for articles published from January 1982 to May 2022. Normalized kicking values were compared using one-way ANOVA. Eighteen articles included FKs (sample: 113 elite men, 109 sub-elite men, and 46 novices), and twenty-five articles included RKs (sample: 238 elite men, 143 sub-elite men, and 27 novice men). The results indicate that the impact force of the FK were 47% (p < 0.01), 92% (p < 0.01), and 120% (p < 0.01) higher than those of the RK across novice, sub-elite, and elite groups, respectively. Moreover, the maximum foot velocity of the RK was 44% (p < 0.01) and 48% (p < 0.01) higher than that of the FK for the sub-elite and elite groups, respectively. Furthermore, the elite group had 65% (p < 0.01) higher knee extension angular velocity with the RK than with the FK and 138% (p < 0.01) higher hip extension angular velocity with the FK than with the RK. In summary, the findings suggest that the FK is more effective in generating forceful kicks, while the RK has the potential for rapid execution.